Investment Resilience in Times of Crisis: The Nexus of Domestic, Foreign Investment, and Interest Rates on Economic Growth amidst The Covid-19 - Hayati, Cucu; Hanifah; Diah Ayu Sanggarwati; Fatchurrohman, Mochamad (Global Economic, Social, and Development Review, 2024)
This study examines the impact of foreign investment, domestic investment, COVID-19, and interest rates on economic growth across 34 provinces in Indonesia from 2010 to 2023, a period encompassing both pre- and post-pandemic phases. The urgency of this research lies in understanding how these factors have influenced regional economic performance, particularly during the COVID-19 pandemic, which disrupted global and local economies. This study uses a Panel data regression model, fixed-effects, and robust standard errors. The result analysis reveals that the regression model explains that 44.33% of the variation in economic growth can be attributed to domestic and foreign investments; and interest rates. The probability test results show that foreign investment significantly affects economic growth more than domestic investment. Interest rates did not significantly impact economic growth during the COVID-19 period, as indicated by the statistical analysis. It implies that despite its potential role in stabilizing the economy, interest rate policies may have been less effective in fostering growth during the pandemic. These findings highlight the critical role of foreign investment and pandemic-related factors in shaping economic growth dynamics in Indonesia provinces.